Polyimide composites containing confined tetragonality high TC PbTiO3 nanofibers for high-temperature energy storage. (1st November 2021) - Jian, Gang; Jiao, Yong; Meng, Qingzhen; Xue, Fei; Feng, Liang; Yang, Ning; Jiang, Jianhua; Lü, Minfeng
Abstract: High temperature (HT) dielectrics have drawn increasing attentions due to strong potentials in capacitors working in extreme temperature conditions. The selection of high temperature ceramic fillers and polymers and the design of composite configurations are crucial for obtaining excellent dielectric and energy storage performances. In this study, PbTiO3 nanofibers with a confined tetragonality with a lower c/a ratio are synthesized by the molten-salt method and polyimide (PI)/PbTiO3 nanofiber composites are prepared via the in-situ polymerization. The composite (50 vol% filler loading) possesses greatly enhanced dielectric constant of 46 and low tanδ of 0.02 at 1 kHz; εr is 13.9 times larger than 3.3 for PI. From electric displacement-electric field loop investigations, superior energy storage performances of a large discharged energy-density of 16 J cm −3 under 300 MV m −1 and a large charge/discharge efficiency of 80 % are obtained. Furthermore, dielectric constant, energy density and efficiency of the composite exhibit a very good thermal stability from the room-temperature to over 200 °C. Overall, superior properties as well as good thermal stabilities of the PI/PbTiO3 nanofiber composites indicate strong potentials in HT electrical energy storage capacitors. Graphical abstract: Image 1 Highlights: PbTiO3 nanofibers with confined c/a ratio of 1.0579 are synthesized. Polyimide/PbTiO3 composite possesses a dielectric constant of 46 at 1 kHz. The composite possesses Ud of 16 J cm −3 and η of 80 % at 300 MV m −1 . High temperature stability is achieved in composites to 200 ° C.